2007
DOI: 10.1139/f07-015
|View full text |Cite
|
Sign up to set email alerts
|

Relating otolith chemistry to surface water chemistry in a coastal plain estuary

Abstract: Although laboratory studies confirm that otoliths incorporate trace elements and stable isotopes from surrounding waters, few studies explore the relationship of otolith chemistry to water chemistry in the field and none include a larger suite of environmental tracers, such as rare earth elements. Using spotted seatrout (Cynoscion nebulosus) as model species, we tested the hypothesis that otoliths record the water chemistry of seagrass habitats in Chesapeake Bay. In summer 2001, we sampled water and juvenile f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 44 publications
7
75
3
Order By: Relevance
“…It was therefore important to determine if water chemistries differed within and among streams and whether these differences were manifested in trout otoliths. We found that elemental signatures of Sr:Ca and Sr isotopes in water samples remained generally constant in seasonal water samples from individual stream sites, which corroborates previous studies in other freshwater systems in North America (Dorval et al 2007;Kennedy et al 2000;Wells et al 2003). The minor seasonal variation in Sr concentrations and isotope compositions of stream waters likely results from basinspecific precipitation and discharge trends and subsequent timing and magnitude of mineral weathering.…”
Section: Discussionsupporting
confidence: 88%
“…It was therefore important to determine if water chemistries differed within and among streams and whether these differences were manifested in trout otoliths. We found that elemental signatures of Sr:Ca and Sr isotopes in water samples remained generally constant in seasonal water samples from individual stream sites, which corroborates previous studies in other freshwater systems in North America (Dorval et al 2007;Kennedy et al 2000;Wells et al 2003). The minor seasonal variation in Sr concentrations and isotope compositions of stream waters likely results from basinspecific precipitation and discharge trends and subsequent timing and magnitude of mineral weathering.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we have observed periods of elevated Mn/Ca ratios in cod otoliths from other areas (North Sea and Norwegian poll fjord) as well as in those of other species (Salmonidae, Clupeidae) in the Baltic and in Oneida Lake, a system known to have elevated Mn and periods of hypoxia. Elevated Mn/Ca ratios in sciaenid fishes in the Pamlico Sound and the Chesapeake Bay were also attributed to redox dynamics (29,30). Given the numerous and large archival collections of cod otoliths, there is potential to gain much better understanding of cod's interaction with hypoxia, particularly in early life, and to aid in designing MPAs that protect all life stages, including juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Campana (1999) list marine fish otoliths as having a mean Mg:Ca ratios of approximately 117 Atmol mo 1 ', while most values in the present study are below 100 jpmol mol-1 . Mollusc shells and corals tend to have even higher Mg:Ca, often above 1 mmol mol' (Carr6 et al, 2006;Shirai et al, 2008) with the calcitic portion of a deep-sea oyster shell reaching values of 22.5 mmol mol "1 (Wisshak et al, 2009); although Rio et al (1992) (Dorval et al, 2007), shells from Chione subrugosa had values as high as 3600 iimol mol "1 (Carr6 et al, 2006) and Acropora nobilis coral skeletons were even higher, ranging up to 9500 pmol mol~' (Shirai et al, 2008), yet the zoarcid values are still substantially higher. Sr:Ca incorporation can be influenced not only by the Sr:Ca concentration of the organisms environment, but also by environmental temperature (Bath et al, 2000;Elsdon and Gillanders, 2002;Richardson et al, 2004) and, at least for molluscs, growth rate (Stecher et al, 1996;Carr6 et al, 2006).…”
Section: -Th25mentioning
confidence: 98%